How immigrant parents can teach their adolescents Islamic values and religious practices in non-Muslim communities - Alalwani, Nada Abdulrahman Eid (Kansas State University, 2018)
Permanently moving from one country to another affects the family. This can include the ways in which parents interact with their children. That interaction can be especially challenging when Muslim families move to primarily non-Muslim Western societies such as the United States. This report reviews challenges, opportunities, and strategies for Muslim parents residing in the United States to embed Islamic values and religious practices with their adolescent children. This report also identifies effective ways for Muslim parents to help their adolescent children understand, accept, and practice the Muslim faith. After a review of scholarly literature and existing Islamic religious practice materials, recommendations are provided to help parents effectively model and support appropriate Islamic religious practice to their adolescent children based on the parents’ traditional Muslim beliefs.
Keywords: Immigrant parents; Adolescents; Islamic values; Muslim family; Parent-child relationship; Religious practices